The J and P transformer book : / a practical technology of the power transformer. - Heathcote, Martin J., ....- (Amsterdam : Elsevier, 2007)
The complete reference for the design, monitoring and maintenance of power transformers - in electricity generation and distribution, electricity substations, and industrial applications.